Accelerating phase-field modeling of solidification with a parallel adaptive computational domain approach. (February 2020) - Ding, Peng; Liu, Zhe
Abstract: We developed a parallel adaptive computational domain method for accelerating the simulation of solidification in two dimensions using the phase-field model. The algorithm is paralled with the MPI library based on the domain decomposition approach. We discuss the implementation details of the parallel adaptive computational domain method and the domain decomposition based strongly implicit linear solver. We examined the performance of our algorithm by comparing with the algorithm based on the fixed computational domain and show that it greatly reduces the computational cost of solving the phase-field model. We also simulate the competitive growth process of the second and ternary dendritic arms successfully.